The Escherichia coli CydX Protein Is a Member of the CydAB Cytochrome bd Oxidase Complex and Is Required for Cytochrome bd Oxidase Activity - VanOrsdel, Caitlin E. (American Society for Microbiology, 2013)
Cytochrome bd oxidase operons from more than 50 species of bacteria contain a short gene encoding a small protein that ranges from ∼30 to 50 amino acids and is predicted to localize to the cell membrane. Although cytochrome bd oxidases have been studied for more than 70 years, little is known about the role of this small protein, denoted CydX, in oxidase activity. Here we report that Escherichia coli mutants lacking CydX exhibit phenotypes associated with reduced oxidase activity. In addition, cell membrane extracts from ΔcydX mutant strains have reduced oxidase activity in vitro. Consistent with data showing that CydX is required for cytochrome bd oxidase activity, copurification experiments indicate that CydX interacts with the CydAB cytochrome bd oxidase complex. Together, these data support the hypothesis that CydX is a subunit of the CydAB cytochrome bd oxidase complex that is required for complex activity. The results of mutation analysis of CydX suggest that few individual amino acids in the small protein are essential for function, at least in the context of protein overexpression. In addition, the results of analysis of the paralogous small transmembrane protein AppX show that the two proteins could have some overlapping functionality in the cell and that both have the potential to interact with the CydAB complex.